2020
DOI: 10.17159/2221-4070/2020/v9i2a5
|View full text |Cite
|
Sign up to set email alerts
|

Using Collages to Change School Governing Body Perceptions of Male Foundation Phase Teachers

Abstract: The paper explores how collages can be used to change school governing body (SGB) members' perceptions of male teachers in the foundation phase (FP) in the Nelson Mandela Metropole, South Africa. The involvement of men in FP teaching forms part of initiatives to diversify and do away with the underrepresentation of men in the early years of learning. SGBs play an integral role in the recruitment and retaining of teachers in schools, but not much is known on how SGBs perceive male teachers and their willingness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This paper is based on a bigger qualitative study in line with Creswell and Creswell (2017). We used participatory visual methodologies such as the creation of collages (see Kagola & Khau, 2020), and participatory methods such as semi-structured focus group conversations to enable SGB parent-component members to share their understandings and experiences in the employment of male FP teachers. In this article, we discuss only the semi-structured focus group conversations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper is based on a bigger qualitative study in line with Creswell and Creswell (2017). We used participatory visual methodologies such as the creation of collages (see Kagola & Khau, 2020), and participatory methods such as semi-structured focus group conversations to enable SGB parent-component members to share their understandings and experiences in the employment of male FP teachers. In this article, we discuss only the semi-structured focus group conversations.…”
Section: Methodsmentioning
confidence: 99%
“…In support of this Msiza (2019) indicated that males seeking employment in such professions like FP teaching is not easy since they are often policed and perceived to have ulterior motives such as wanting to engage in paedophiliac behaviour (Mashiya et al, 2015;Moosa & Bhana, 2018;Msiza, 2019). The male teachers' masculinity is also questioned and at times they are belittled (Kagola & Khau, 2020;Msiza, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…The positioning of FP as suitable work for women is underpinned by the assumption that FP teaching is care work and that women are better carers than men (Msiza, 2020). Kagola and Khau (2020), in their study on school governing bodies, found that gender played a significant role in the division of labour, particularly in the employment of FP teachers. Bhana (2016) posited that the maintenance of a gendered division of labour in FP functions as a mechanism to disassociate men from working in this educational phase.…”
Section: Queering the Foundation Phasementioning
confidence: 99%